Long-standing Multifocal Motor Neuropathy Presenting With Delayed Clinical Features of Anti–Myelin-Associated Glycoprotein Neuropathy and Elevated Anti–Myelin-Associated Glycoprotein Antibody Titers. Issue 3 (March 2021) - Bernardo, Katrina A.; Weiss, Michael D.
Abstract: Multifocal motor neuropathy with conduction block (MMN) and anti–myelin-associated glycoprotein (MAG) neuropathy are rare chronic acquired demyelinating neuropathies with distinct clinical and electrophysiological characteristics. These neuropathies are generally not known to coexist. This report describes a patient with long-standing MMN who subsequently developed clinical features of anti-MAG neuropathy. This suggests that subtypes of chronic inflammatory neuropathies may not be sharply defined. In addition, a presentation of MMN with anti-MAG titers may be a prognostic indicator of poor response to standard MMN treatment.